Pui Tak Center partners with library to explore the world. (Illinois Literacy)
Reports on a community event called Around the World in Fifteen Minutes organized by the Family Literacy Project at the Pui Tak Center and the Chicago Public Library in Chinatown, Chicago in Illinois in 2006. Representation of areas of the world by the booths, including Africa; Participation of children in coloring a world map; Development of the leadership skills among parents who planned the event.